(untitled) (Revista de Defesa da Concorrência, 2021)
The object of the paper is to investigate the competition in digital markets and the role of competition policy in developing economies for an inclusive growth and shared prosperity with innovative tools for a better competition law enforcement. Its methodology analyses international reports and surveys. Developing economies must strengthen their capacity to design competition policy in the digital markets according to their individual social and economic development particularities, observing what developed economies have been doing in their own market. EU has been driving the competition policy in digital markets evaluating mergers and acquisition and prosecuting abuse of dominance. The Digital Markets Act and the Digital Services Act are two more initiatives able to facilitate developing economies in designing their own regulation in digital markets. The result of the paper indicates that one size does not fit all and as a conclusion, experience and good standards should be evaluated and tailored.